60s Bremensketching - A Practical Workshop - Ramos, M.; Afonso, A. (Visionary Anthropology - 10 June 2017 - Teerhof, Guesthouse of the University of Bremen, 2017)
Whether in form of individual discoveries, political far-sightedness, visions of the future or intuition – the visionary has always played a key role in people’s lives, as a motor of individual change and as an impulse for social change. Both real contestation and imagined alternatives are incited by moments of inspiration sparked by inner voices or fantasy, by interaction or friction. Such ideas trigger the emergence of social movements and trouble them. Counter-movements and dystopias give rise to unsettling tensions, which in turn may create something new. These processes of innovation and creativity do not always occur consciously, but are rather entangled within the practices of the everyday. “Liminality” or “serendipity” are the concepts used by anthropologists to grasp this potentially unpredictable and highlight the socio-cultural relevance of this dimension of human action. The visionary is also what guides us as ethnographers and cultural theorists in shaping our discipline. Methodological innovations often result from the necessity to create alternative forms of understanding and new tools of translation where the previous methods have reached their limits, or to experiment with other forms of cooperation and representation. Similarly in teaching, questions of curious students, stalemates in discussions, a spontaneous change of topic or the feedback of a working group are moments opening up opportunities for change. What are the sources of inspiration, the unanswered questions or key concepts we should be lead by in order to constitute and convey a contemporary anthropology?